Sistem Peradilan Pada Kerajaan Arab Saudi - Gilang Rizki Aji Putra (ADALAH, 2022)
Judicial bodies in countries exhibit enormous differences and variations. The judicial system and its organization in countries are closely related to the history of the country concerned. The organizational structure of judicial power varies from one country to another. Differences in the composition of judicial power also occur because of the shape of the state, for example in the form of a federation and a royal state. The composition of judicial power in a federal state is reflected in the organizational structure and jurisdiction of the judiciary, such as in Malaysia, while the organizational structure of judicial power in a royal state is reflected in the organizational structure of judicial power, such as in Saudi Arabia. Saudi Arabia's judiciary can be one of the choices of the modern justice system and it is interesting to study because of several things, first of all, Saudi Arabia is the birthplace of the Prophet Muhammad SAW. and Islam is a role model for people around the world, but this country has a different government system from other Muslim countries.